PEMBARUAN HUKUM PIDANA MELALUI AKTUALISASI NILAI-NILAI PANCASILA BERORIENTASIKAN PENDEKATAN RELIGIUS - Fatoni, Syamsul (Ahkam: Jurnal Hukum Islam, 2015)
The reformation of criminal law can be done through the reformation of substantial norm as well as the reformation of cultural value including Pancasila. Therefore, it is emergent to explore the law which is based on cultural value, morality, and religion including reactualization of Pancasila to maintain a harmonious life. Kata kunci: Pembaruan, Nilai-Nilai Pancasila, Religius